Replicating "Predicting the present with Google trends" by Hyunyoung Choi and Hal Varian (The Economic Record, 2012) - Tom Coupé (Kiel Institute for the World Economy (IfW), 2017)
In this note, the author describes different ways one could try to replicate Choi and Varian (Predicting the present with Google trends, The Economic Record, 2012).
Keywords: A1; C1; C8; C53; 330; Replication